Rapid assessment of avoidable blindness and diabetic retinopathy in people aged 50 years and older in the National Capital District of Papua New Guinea. Issue 6 (4th July 2018) - Burnett, Anthea; Lee, Ling; D'Esposito, Fabrizio; Wabulembo, Geoffrey; Cama, Anaseini; Guldan, Georgia; Nelisse, Marleen; Koim, Samuel Peter; Keys, Drew; Poffley, Alison J; Limburg, Hans; Garap, Jambi
Abstract : Background/aims: To conduct an assessment of avoidable blindness, diabetes mellitus and diabetic retinopathy (DR) in adults aged 50 years and older in the National Capital District (NCD) region of Papua New Guinea (PNG). Methods: A cross-sectional population-based survey was performed for which 25 clusters of 50 people aged ≥50 years were randomly selected from the NCD region. The standardised rapid assessment of avoidable blindness (RAAB) with diabetic retinopathy (+DR) methodology was used. Blindness was defined as presenting visual acuity <3/60 in the better eye. Participants were classified as having diabetes if they were known to have diabetes or if their random blood glucose level was ≥200 mg/dL. Dilated fundus examination and Scottish DR grading were performed. Results: In total, 1192 out of 1250 eligible participants (95.4%) were examined. Of these, 7.8% had known or newly diagnosed diabetes. Seventy-one per cent of participants with known diabetes had a blood glucose level ≥200 mg/dL, and 82.9% had never had an ophthalmological examination for DR. Prevalence of DR and/or maculopathy was 46.4%. The age-adjusted and sex-adjusted prevalence of diabetes was estimated at 8.1% (95% CI 5.7% to 10.4%) in the population aged 50 years or older in the NCD region of PNG. Conclusions: Prevalence of diabetes in adults aged 50 years and older was lower than reported elsewhere in the region, and lower than other RAAB+DR surveys. Despite this, the prevalence of DR is high compared with other RAAB+DR surveys and demonstrates the need for increased awareness and accessibility to eye services for people with diabetes.